A Strategy for Long Run Development of Lithuanian Economy - Vilkas, Eduardas (Ekonomika, 1999)
The paper aims to describe a strategy for promotion of economic growth in Lithuania. Description of the strategy in some detail is a rather considerable work and would need cooperation with experts in many fields of economy. The paper thus is an introduction to the strategy formulation trying to outline the main features of development policies. Most importantly, we try to stress the views of modem economic theories on long run growth according to which decisive contribution to economic growth belongs to knowledge and existence of respective incentives whereas growth of investment and labor force without technological upgrading have minor role. Development of high-technology production is necessary condition to achieve high standard of living. Lithuania has all needed components to start that development without delay; some features of the corresponding program are presented. Prospects of Lithuania’s economic growth in medium tenn are also outlined for the main sectors of real production. Here, utilization of idle capital capacities and unemployed labor force are serious source of immediate economic growth.